Enzyme‐Degradable Self‐Assembled Hydrogels From Polyalanine‐Modified Poly(ethylene glycol) Star Polymers. Issue 3 (3rd January 2013) - Thornton, Paul D.; Billah, Shah M. Reduwan; Cameron, Neil R.
Abstract The generation of a range of star‐shaped block copolymers composed of a biocompatible poly(ethylene glycol) (PEG) core tethered to a polyalanine (PAla) shell that possesses the capability to (reversibly) self‐assemble in water is described. The hydrogels formed offer a hydrophilic environment ideal for biological processes involving proteins and are able to withhold albumin for prolonged periods before its triggered release following the targeted material degradation by the proteolytic enzyme elastase. Consequently, the materials formed offer significant promise for the delivery of proteins, and possibly inhibitors, in response to a proteolytic enzyme overexpressed in chronic wounds.